Flow-induced glycocalyx formation and cell alignment of HUVECs compared to iPSC-derived ECs for tissue engineering applications - Lindner, Marcus; Laporte, Anna; Elomaa, Laura; Lee-Thedieck, Cornelia; Olmer, Ruth; Weinhart, Marie (Frontiers in Cell and Developmental Biology, 2022)
The relevance of cellular in vitro models highly depends on their ability to mimic the physiological environment of the respective tissue or cell niche. Static culture conditions are often unsuitable, especially for endothelial models, since they completely neglect the physiological surface shear stress and corresponding reactions of endothelial cells (ECs) such as alignment in the direction of flow. Furthermore, formation and maturation of the glycocalyx, the essential polysaccharide layer covering all endothelial surfaces and regulating diverse processes, is highly dependent on applied fluid flow. This fragile but utterly important macromolecular layer is hard to analyze, its importance is often underestimated and accordingly neglected in many endothelial models. Therefore, we exposed human umbilical vein ECs (HUVECs) and human induced pluripotent stem cell-derived ECs (iPSC-ECs) as two relevant EC models in a side-by-side comparison to static and physiological dynamic (6.6 dyn cm-2) culture conditions. Both cell types demonstrated an elongation and alignment along the flow direction, some distinct changes in glycocalyx composition on the surface regarding the main glycosaminoglycan components heparan sulfate, chondroitin sulfate or hyaluronic acid as well as an increased and thereby improved glycocalyx thickness and functionality when cultured under homogeneous fluid flow. Thus, we were able to demonstrate the maturity of the employed iPSC-EC model regarding its ability to sense fluid flow along with the general importance of physiological shear stress for glycocalyx formation. Additionally, we investigated EC monolayer integrity with and without application of surface shear stress, revealing a comparable existence of tight junctions for all conditions and a reorganization of the cytoskeleton upon dynamic culture leading to an increased formation of focal adhesions. We then fabricated cell sheets of EC monolayers after static and dynamic culture via non-enzymatic detachment using thermoresponsive polymer coatings as culture substrates. In a first proof-of-concept we were able to transfer an aligned iPSC-EC sheet to a 3D-printed scaffold thereby making a step in the direction of vascular modelling. We envision these results to be a valuable contribution to improvements of in vitro endothelial models and vascular engineering in the future.